Comparison of Immature Platelet Fraction (IPF) Values for ACS Patients with Unstable Angina Pectoris (UAP), Non-ST Elevation Myocardial Infarct (NSTEMI), and ST Elevation Myocardial Infarct (STEMI) - Siregar, Fadhilaturrizqie; Husni; Deswita Sari (HM Publisher, 2024)
Background: Acute coronary syndrome (ACS) is a medical emergency that requires rapid diagnosis and treatment. Immature platelet fraction (IPF) is a hematological parameter that has the potential to be a biomarker for differentiating types of ACS. This study aims to compare IPF values in ACS patients with unstable angina pectoris (UAP), Non-ST elevation myocardial infarction (NSTEMI), and ST-elevation myocardial infarction (STEMI). Methods: This research is an analytical observational study with a cross-sectional design. The research subjects were ACS patients treated at Dr. M. Djamil General Hospital, Padang, Indonesia between January 2023 to December 2023. IPF values were measured using the Sysmex XN-1500 tool. Statistical analysis was carried out using the ANOVA test and post-hoc Tukey test. Results: A total of 150 ACS patients (50 UAP, 50 NSTEMI, 50 STEMI) were included in this study. The mean IPF value in the STEMI group (6.8 ± 2.1%) was significantly higher than that in the NSTEMI (4.5 ± 1.8%) and UAP (3.2 ± 1.5%) groups (p < 0.001). ROC analysis showed that the IPF value had an AUC of 0.89 (95% CI: 0.84-0.94) for differentiating STEMI from NSTEMI/UAP. Conclusion: IPF values were higher in STEMI patients compared to NSTEMI and UAP. This parameter has the potential to be a biomarker for differentiating types of ACS, especially in differentiating STEMI from NSTEMI/UAP.